Legal Review Concerning Summary of Office of Notary & Land Asset Officers Who Are Not Uniting Area of Work - Bima Pradana (Program Studi Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam SUltan Agung, 2021)
Notary is a promising legal profession. Of course there are some special competencies that must be met to become a notary. In other words, it is impossible for a notary to practice without having sufficient skills. Legal education background is a must. Postgraduate education in notary law must be preceded by taking a bachelor's degree in law. Notary is a public official who has the authority to make an authentic deed. This has been regulated in the provisions of Article 1 of the Law on the Position of Notary Public (hereinafter abbreviated as UUJN).